Organic–inorganic assembly engineering of core–double-shell VSe1.6/C@N–C⊂MoSe2 nanotubes for boosting Na+/K+ storage performance. Issue 35 (22nd August 2022) - Kang, Wenpei; Han, Xihao; Wang, Xiaotong; Zhu, Zongfan; Zhang, Bingchen; Wang, Zhurui; Wang, Yuyu; Sun, Daofeng
Abstract : Core–double-shell VSe1.6 /C@N–C⊂MoSe2 nanotubes are designed through a template-directed strategy and demonstrated as a high-performance host for Na + /K + ions. Abstract : Core–shell structures with gradient components are considered as promising active materials for energy storage systems because of their prominent synergistic effects and enhanced reaction kinetics. In this work, gradient-structured VSe1.6 /C@N–C⊂MoSe2 nanotubes, with VSe1.6 /C inner cores, and double shells of protecting N–C layers and an activated MoSe2 outer shell, are prepared through a high-temperature selenization process of a tailored template, which are obtained from an organic–inorganic assembly process. As for the storage of the large-sized Na + /K + ions, this ingenious structure of VSe1.6 /C@N–C⊂MoSe2 nanotubes can markedly enhance the reaction kinetics and well balance the reaction activity and cycling stability, due to increased ion/electron diffusion channels from the MoSe2 and N–C shells, abundant internal interfaces and gradient-component distribution. As a result, a capacity of 232.4 mA h g −1 over 10 000 cycles can be retained at a current of 5.0 A g −1, with a capacity retention of 86.8%. As for potassium ion batteries (PIBs), VSe1.6 /C@N–C⊂MoSe2 nanotubes deliver a high and stable capacity of 180 mA h g −1 at 1.0 A g −1 for 5000 cycles with a capacity retention of 71.3%. Based on d Q /d V analysis and ex situ XRD results, the VSe1.6 /C@N–C⊂MoSe2 anode has a hybrid mechanism of MoSe2 (intercalation and conversion reactions) and VSe1.6 (only intercalation reaction) and high reversibility for K + storage. And combined with the component and structural superiorities, high cycling stability can be achieved for the VSe1.6 /C@N–C⊂MoSe2 nanotubes in PIBs.